Pengaruh Kemampuan Literasi Hard Skill dan Soft Skill terhadap Self Efficacy Mahasiswa pada Pengguna Platform Digital Job Seeker (Study Kasus Mahasiswa Aktif dan Alumni Universitas Pancasakti Tegal) - Faiz Irsyad Prasetyo; Deddy Prihadi; Dewi Indriasih; Febri Yoga Sapta Raharjo; Elsa Kholifatul Nur Rachmadani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The market in the current digital era is very broad, which can be seen from the many Job Seeker-based platforms or applications. Universities are actually one of the largest producers of competent workforce, of course they need to create a strong character. Higher education can be a forum for the creation of Hard Skills and Soft Skills which can produce high Self Efficacy so that links and matches can be created in the labor market. This research aims to find out whether Hard Skills and Soft Skills have a positive effect on Self Efficacy among job seeker platform users. This research uses the explanatory type. The sampling method used is non-probability sampling with a convenience sampling approach which is distributed online via Google form. A total of 80 active students and alumni of Pancasakti University Tegal using the Job Seeker Platform were used as research samples with a measurement scale using a Likert scale. The data analysis and processing used in this research uses descriptive analysis and Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) method. The results of this research show that Hard Skills and Soft Skills influence Self Efficacy.